Linguistic Approach for Estimation of Electrocardiograms’s Subtle Changes Based on the Levenstein Distance - Fainzilberg, L.S.; Dykach, Ju.R. (Кибернетика и вычислительная техника, 2019)
The purpose of the article is to develop algorithmic and software components to solve this problem and conduct experimental studies on model and real data. Methods. ECG of certain groups was automatically encoded, Levenshtein distance was calculated between ECG pairs for group and the reference codogram of the group was constructed. The evaluation of the results of experimental studies was carried out on the basis of traditional methods of statistical analysis. Results. It is shown that based on the Levenshtein distance between all pairs of codograms of the test group, the reference codogram of the group of patients with coronary artery disease (CAD) and the group of healthy volunteers can be determined. It was established that making decisions based on the comparison of the ECG codogram of the person with the reference codogram allows for the separation of representatives of the indicated groups with sensitivity SE = 72% and specificity CP = 79% even in those cases when the traditional analysis of the ECG in 12 leads is not informative.